Cardio-metabolic risk profile of people living with HIV: Is retinal microvascular geometric morphology a marker of effect? - Kgokane, Boipelo Mirriam Lepetjia (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.